Case report: The Circle Game - Yue, Yu Chen; Glancy, Graham (Frontiers in Psychiatry, 2023)
The authors present a rare case of a family in which both the mother, and four decades later the son, committed second-degree murder while suffering from major mental illnesses. The mother had successfully used a mental disorder defence and it was likely that the son who had raised the defence would have qualified also. The mother has a history of adverse childhood experiences. The son had also experienced various severe childhood adversities, though there were no functional impairments, personality dysfunction, suicidality or violent crimes until the onset of treatment-resistant schizoaffective disorder around age 18. His earlier comorbidities included sport-related traumatic brain injuries, sickle cell trait, severe burns, and tardive dyskinesia. His comorbidities around the material time included occasional cannabis use and dementia pugilistica. While awaiting court ruling on criminal responsibility, additional stressors triggered significant deterioration of his schizoaffective disorder and the court found him unfit to stand trial. During rehabilitation, he was severely injured by another accused, which subsequently led to his demise. This case is the first report of intergenerational mental disorder defence and involved almost every facet of criminal forensic psychiatry, which highlights the need for further research on the association between intergenerational ACEs and intergenerational risk for criminal behaviour from a comprehensive and longitudinal perspective.